The Cultural Resistance of K.H. Sholeh Darat Against Colonialism Through a Hidden Transcript Perspective - Muhamad Ichrom; Imam Yahya; Agus Nurhadi; Mirza Mahbub Wijaya; Mowafg Masuwd (Universitas Darussalam Gontor, 2026)
Dutch colonialism extended beyond political and economic domination, aiming also to control religious and cultural spheres through education and the promotion of Latin scripts. The central problem this study addresses is how K.H. Sholeh Darat employed religious and cultural practices as strategies of resistance against colonial hegemony. This study aims to analyze the forms of cultural resistance employed by K.H. Sholeh Darat within the framework of James C. Scott’s Hidden Transcript theory. This research uses a library-based method with a qualitative analytical approach. Data analysis is conducted using the framework of Hidden Transcript to explore the interplay among public transcripts, hidden transcripts, and everyday forms of resistance. The findings reveal that K.H. Sholeh Darat’s use of Arabic Pegon in his Islamic texts served as a medium for transmitting religious values embedded with implicit messages of Islamic nationalism. This symbolic resistance effectively preserved local identity and fostered cultural and national consciousness among Javanese Muslims. In conclusion, Sholeh Darat’s resistance was non-confrontational yet ideologically powerful, affirming James C. Scott’s theory that dominated groups can construct hidden spaces of resistance through symbolic and cultural expressions in everyday life.